'Well, This is it. Just Get on With it': Pain Willingness and Activity Engagement in People with Chronic Pain. Issue 1 (July 2016) - Titus, Cecelia A.; Biggs, Herbert C.
Abstract : Acceptance of chronic pain is associated with positive health outcomes. The study examined participants' chronic pain experiences by exploring two acceptance factors: pain willingness and activity engagement. Eleven participants (seven women and four men) participated in semi-structured interviews. Interview transcripts were analysed to identify pain willingness and activity engagement in participants' experiences. The study found that participants demonstrated some pain willingness and activity engagement, but that avoidance and control could result in unwanted activity restrictions. Three themes were identified in participants' accounts of getting on with their lives: making necessary adjustments, taking control and finding purpose and meaning. To improve outcomes for people with chronic pain, counsellors and rehabilitation professionals should encourage pain acceptance, and educate their clients about the effects of social withdrawal, and avoidance and control of pain.